Malaysian risk management committees and firms’ financial performance / Roslida Ramlee and Normah Ahmad - Ramlee, Roslida; Ahmad, Normah (Accounting Research Institute (ARI), 2020)
The establishment of a risk management committee (RMC) as a board committee is mandatory for finance firms in Malaysia. But for firms in the non-finance sector, the practice is still voluntary. This study examined (1) the roles and responsibilities of RMC on Malaysian non-finance firms and (2) the relationship between RMC and firms’ financial performance. The data collected were from the corporate annual reports and for the period 2009 – 2016. Firms’ financial performance was measured by return on assets (ROA), return on equity (ROE) and Tobin’s Q. The RMC were proxied by five (5) characteristics: its size, its independence, the existence of CEO/ COO/CRO/CFO on RMC, their knowledge and expertise, and frequency of RMC meetings. The data were analyzed using the Panel Data Analysis Stata13. This study found that the responsibilities of RMC vary from simple reviewing and risk categorizing to approving risk strategies, reporting to the board of directors and providing assurance on the risk management process. This study showed that the existence of CEO/COO/CRO/CFO on RMC and their knowledge and expertise are associated with firms’ financial performance. This study concluded that though RMC in non-finance firms is a voluntary practice, their establishment is one of the important strategies of corporate governance reform.